Effect of Addition of ESCM and ESM during In Vitro Maturation on In Vitro Development of Porcine Follicular Oocytes - Seok-Gi Kim; Hum-Dai Park (The Korean Society of Animal Reproduction and Biotechnology, 2019)
In this study, we investigated the possibility of using mouse embryonic stem cell conditioned medium (ESCM) and embryonic stem cell medium (ESM) for in vitro maturation in the efficient in vitro production of blastocysts from porcine follicular oocyte. Depending on the concentration of supplement of ESCM added to the NCSU-23 solution did not affect 2-cell development rates and blastocysts development. However, in particular, the survival rate (10 days of culture) of blastocyst was significantly higher than that of the control group as the additive concentration (30%) increased (p < 0.05). The survival rate of blastocysts showed a similar tendency even with addition of ESM (30%) alone. On the other hand, the duration of the addition of these additives during IVM (0-44 h) was that the IVM I period (0-22 h) were more effective than the IVM II period (22-44 h). Thus, the effect of these additives is probably due to the combination of the various physiologically active substances of ESCM or the appropriate amino acids and vitamins of ESM. In particular, these additives were more effective during the first half (IVM I) of in vitro maturation. In summary, optimization of ESCM or ESM supplementation may improve in vitro maturation of porcine oocyte and affect developmental competency. Therefore, if more efficient methods of adding ESCM or ESM to basal culture medium can be developed during in vitro maturation of porcine follicle oocytes, high quality blastocysts will be developed from low porcine follicular oocyte compared to other domestic animals.